A study of chlorinated solvent contamination of the aquifers of an industrial area in central Italy: a possibility of bioremediation - Matteucci, Federica; Ercole, Claudia; del Gallo, Maddalena (Frontiers in Microbiology, 2015)
Perchloroethene, Trichloroethene, and other chlorinated solvents are widespread groundwater pollutants. They form Dense Non Aqueous Phase Liquids (DNAPLs) that sink through permeable groundwater aquifers until non-permeable zone is reached. In Italy there are many situations of serious contamination of groundwater that might compromise their use in industry, agriculture, private, as the critical case of a Central Italy valley located in the province of Teramo (“Val Vibrata”), characterized by a significant chlorinated solvents contamination. Data from the various monitoring campaigns that have taken place over time were collected, and new samplings were carried out, resulting in a complete database. The data matrix was processed with a multivariate statistic analysis (in particular Principal Components Analysis, PCA) and was then imported into Geographic Information System (GIS), to obtain a model of the contamination. A microcosm anaerobic study was utilized to assess the potential for in situ natural or enhanced bioremediation. Most of the microcosms were positive for dechlorination, particularly those inoculated with a mineral medium. This indicate the presence of an active native dechlorinating population in the subsurface, probably inhibited by co-contaminants in the groundwater, or more likely by the absence or lack of nutritional factors. Among the tested electron donors (i.e., yeast extract, lactate, and butyrate) lactate and butyrate enhanced dechlorination of chlorinated compounds. PCA and GIS studies allowed delimiting the contamination; the microcosm study helped to identify the conditions to promote the bioremediation of the area.